2012
DOI: 10.1016/j.pain.2012.07.023
|View full text |Cite
|
Sign up to set email alerts
|

The burden of chronic pain: A cross-sectional survey focussing on diseases, immigration, and opioid use

Abstract: Chronic pain is currently considered a public health problem with high costs to the individual and society. To improve prevention and treatment of chronic pain, epidemiologic studies are mandatory for assessing chronic pain. The aims of this study were to estimate the prevalence of chronic pain in the adult Danish population and to analyze associated factors such as diseases, immigration, and opioid use. This cross-sectional survey combines individual-based information from the Danish Health Survey (2010) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
87
2
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(112 citation statements)
references
References 26 publications
18
87
2
5
Order By: Relevance
“…Similar findings applied to self-reported chronic pain where increased prevalence and higher pain intensity were reported among non-Western immigrants compared with ethnic Danes [21,29,37], yet, one study found no differences in pain report between immigrants holding a Danish citizenship and ethnic Danes [19].…”
Section: Adultsmentioning
confidence: 62%
“…Similar findings applied to self-reported chronic pain where increased prevalence and higher pain intensity were reported among non-Western immigrants compared with ethnic Danes [21,29,37], yet, one study found no differences in pain report between immigrants holding a Danish citizenship and ethnic Danes [19].…”
Section: Adultsmentioning
confidence: 62%
“…26.8% of adult Danes reported that they have chronic pain defined by the question “Do you have chronic/long-lasting pain lasting 6 months or more?” [25]. In contrast, the prevalence of chronic pain might be higher in Asia and lower in New Zealand.…”
Section: Discussionmentioning
confidence: 99%
“…2 In addition, the misuse, abuse and diversion of these medications lead to significant individual and societal burdens. 3 Therefore, there is a continuing quest for opioid analgesics that are as efficacious as existing ones, but have less adverse effect or abuse potential. 4,5 Research over the last few decades has advanced the understanding of the cellular actions of opioid compounds.…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…They were originally named for either a selective ligand (l for morphine, j for ketocyclazocine) or a tissue (d for vas deferens) with which, or in which, it was best characterized. More modern terminology includes OPRM, MOR, MOP or OP 3 ; OPRD, DOR, DOP or OP 1 ; and OPRK, KOR, KOP or OP 2 (among several others) for the l-opioid receptor (protein), the d-opioid receptor (protein) and the j-opioid receptor (protein), respectively. The human genes are designated OPRM, OPRD and OPRK, respectively.…”
Section: Basic Pharmacologymentioning
confidence: 99%